Izračun kontaktnih temperatur v fretinških razmerah - Kalin, Mitjan (Strojniški vestnik, 2001)
The wear and friction properties of tribological interfaces are closely linked to the contact temperature and a knowledge of this temperature is of great interest for tribological applications. The many different temperature-calculation methods that are available in the literature are based on quite different psysical, dynamic and geometric assumptions. As a consequence, large disrepancies in the results can be obtained for the some contact conditions. Although this is a well-known fact, it is sometimes overlooked. In this paper the effects at a tribological interface between silicon nitride and steel under unlubricated and boundary-lubricated fretting conditions were studied. The effects of a change in the contact's thermal properties, as well as its coefficient of friction and the real contact area on the calculated flash temperature are presented. Ten different ready-to-use theoretical models were selected for the purposes of this investigation. The results show a significant difference between the various models, and in particular, the critical importance of the tribological interface properties on the calculated temperatures.
Keywords: modeli; temperature; izračuni; fretting; tribologija; freting obraba